Identification and characterization of short leader and trailer RNAs synthesized by the Ebola virus RNA polymerase - Simone Bach (Public Library of Science (PLoS), 2021)
Transcription of non-segmented negative sense (NNS) RNA viruses follows a stop-start mechanism and is thought to be initiated at the genome’s very 3’-end. The synthesis of short abortive leader transcripts (leaderRNAs) has been linked to transcription initiation for some NNS viruses. Here, we identified the synthesis of abortive leaderRNAs (as well as trailer RNAs) that are specifically initiated opposite to (anti)genome nt 2; leaderRNAs are predominantly terminated in the region of nt ~ 60–80. LeaderRNA synthesis requires hexamer phasing in the 3’-leader promoter. We determined a steady-state NP mRNA:leaderRNA ratio of ~10 to 30-fold at 48 h after Ebola virus (EBOV) infection, and this ratio was higher (70 to 190-fold) for minigenome-transfected cells. LeaderRNA initiation at nt 2 and the range of termination sites were not affected by structure and length variation between promoter elements 1 and 2, nor the presence or absence of VP30. Synthesis of leaderRNA is suppressed in the presence of VP30 and termination of leaderRNA is not mediated by cryptic gene end (GE) signals in the 3’-leader promoter. We further found different genomic 3’-end nucleotide requirements for transcription versus replication, suggesting that promoter recognition is different in the replication and transcription mode of the EBOV polymerase. We further provide evidence arguing against a potential role of EBOV leaderRNAs as effector molecules in innate immunity. Taken together, our findings are consistent with a model according to which leaderRNAs are abortive replicative RNAs whose synthesis is not linked to transcription initiation. Rather, replication and transcription complexes are proposed to independently initiate RNA synthesis at separate sites in the 3’-leader promoter, i.e., at the second nucleotide of the genome 3’-end and at the more internally positioned transcription start site preceding the first gene, respectively, as reported for Vesicular stomatitis virus. Author summary The RNA polymerase (RdRp) of Ebola virus (EBOV) initiates RNA synthesis at the 3’-leader promoter of its encapsidated, non-segmented negative sense (NNS) RNA genome, either at the penultimate 3’-end position of the genome in the replicative mode or more internally (position 56) at the transcription start site (TSS) in its transcription mode. Here we identified the synthesis of abortive replicative RNAs that are specifically initiated opposite to genome nt 2 (termed leaderRNAs) and predominantly terminated in the region of nt ~ 60–80 near the TSS. The functional role of abortive leaderRNA synthesis is still enigmatic; a role in interferon induction could be excluded. Our findings indirectly link leaderRNA termination to nucleoprotein (NP) availability for encapsidation of nascent replicative RNA or to NP removal from the template RNA. Our findings further argue against the model that leaderRNA synthesis is a prerequisite for each transcription initiation event at the TSS. Rather, our findings are in line with the existence of distinct replicase and transcriptase complexes of RdRp that interact differently with the 3’-leader promoter and intiate RNA synthesis independently at different sites (position 2 or 56 of the genome), mechanistically similar to another NNS virus, Vesicular stomatitis virus.